Fiscal Policy for Growth and Development in Tajikistan - Brownbridge, Martin; Canagarajah, Sudharshan (World Bank, Washington, DC, 2012)
Tajikistan's economy has recovered strongly after the collapse of the 1990s, but sustaining rapid economic growth over the long term and reducing poverty present major challenges for policymakers. This paper contributes to the debate over the strategic role for fiscal policy to play in meeting these challenges, utilizing the "fiscal space" approach to assess the long-term potential for expanding public provision of growth-promoting goods and services and evaluating the priorities for public spending. It also analyzes the long-term risks to fiscal sustainability, from external public debt and the quasi fiscal deficit of the electricity sector. The paper contends that institutional reforms in key areas, notably public financial management, tax administration, and the energy sector, are crucial for generating fiscal space and for ensuring that higher levels of public spending are translated into stronger economic growth and poverty reduction. The priorities for government spending should be education, health, and the maintenance of the core networks of the existing infrastructure for energy and transport, rather than new public investment projects.